Reward system practices & employees’ job performance at Jabatan Kerja Raya Melaka Tengah, Melaka / Ahmad Fakhri Mohd Fauzi and Nurul Syazwani Shafery - Mohd Fauzi, Ahmad Fakhri; Shafery, Nurul Syazwani (Faculty of Administrative Science and Policy Studies, 2014)
In this study, the researchers are focus on the reward system and job performance at Jabatan Kerja Raya Melaka Tengah. The purpose of the study is to examine whether there is any relationship between reward system and job performance among employees’ at Jabatan Kerja Raya Melaka Tengah and to identify which element of reward system that influence most towards job performance at Jabatan Kerja Raya Melaka Tengah. This research emphasize on the purpose of conducting by examining several element that lead to the job performance among employees’. In this research it focus on three element of reward system which are transparency of the reward system, fairness of the reward system and employees’ preference on the reward system. For this study, the researchers use the purposive sampling and from 150 populations the sampling is 108 respondents. In this study several methods used like reliability test, normality test, the Spearman’s Rank Correlation and also multiple regression analysis. The findings shows that all three elements have positive relationship and can influence employees’ job performance. It is identified and determined that the transparency of reward system practices is the most important element of reward system practices that affect JKR Melaka Tengah employee’s job performance.